The Greenland mummies - Hart Hansen, Jens Peder; Meldgaard, Jørgen; Nordqvist, Jørgen (McGill-Queen's University Press, 1991)
How did they die? Why were they buried together? What had been the nature of their culture and beliefs? How had they survived in the harsh Arctic climate? To solve this icy mystery, a team of archaeologists, historians, and medical specialists used modern, innovative investigative techniques. They carried out their detective work with keen scholarly curiosity, combined with respect for these people of the past. While many puzzles have been answered, others remain unsolved. The investigation has revealed that the younger child was buried alive at the age of only six months, while the other, two and a half years old, had been born with Down's syndrome. Analysis of the hair of the mummies revealed evidence of air pollution at levels similar to those of today. Speculating on reasons for a mass grave -- a form of burial the Inuit normally used only because of some catastrophe -- the researchers have reconstructed the possible events of the past. The contents of the grave shed light on the every-day life of these people, allowing the investigators to place this evidence within the larger context of Thule culture and knowledge of Inuit contact with the Norse settlements which dotted the outer margins of Greenland during the medieval era. The Greenland Mummies brings the compelling story of this fervent collaboration to the attention of the world. Not only does it provide a fascinating and insightful look into the life and culture of the Inuit in the fifteenth century, it offers an impressive testament to one of the most successful archaeological investigations ever conducted.